Fibromyalji Sendromlu Hastalar ile Sağlıklı Bireylerin Fiziksel Aktivite ve Fiziksel Uygunluk Düzeyi Farkları - (:unkn) unknown (My University, 2017)
Amaç: Çalışmanın amacı fibromyalji sendromlu (FMS) hastalarda fiziksel aktivite ve fiziksel uygunluk düzeyini belirlemek ve sağlıklı bireylerin verileri ile karşılaştırmaktır. Yöntemler: Çalışmaya 82 fibromyalji hastası ve 110 sağlıklı olgu dahil edildi. Fiziksel aktivite düzeyini karşılaştırmak için tüm olgular Uluslararası Fiziksel Aktivite Anketi'nin (UFAA) uzun formatını cevaplandırdılar. Olguların sağlıkla ilişkili fiziksel uygunluk düzeyini belirlemek için vücut kompozisyonu, kassal endurans, kardiorespiratuar endurans esneklik ve denge ölçümleri değerlendirildi. Vücut kitle indeksi, mekik testi, 6 dakika yürüme testi, otur-uzan test, gövde lateral fleksiyon, KAT 3000 testleri sırasıyla vücut kompozisyonu, kassal endurans, kardiorespiratuar endurans, esneklik ve dengeyi belirlemek için kullanıldı.Bulgular: FMS'li hastaların %36,6'sı aktif, %45,1'i minimal aktif, %18,3'ü aktifti. Sağlıklı olguların %40,9'u aktif, %36,4'ü minimal aktif, %22,7'si inaktifti. Gruplar arasında UFAA yürüme ve toplam skoru arasında istatistiksel olarak anlamlı fark bulundu (p<0,05). Sağlıkla ilişkili fiziksel uygunluk düzeyinde mekik testi (p<0,001) ve her iki gövde lateral fleksiyonu (p<0,001) skorunda fibromyalji ve kontrol grubu arasında istatistiksel olarak anlamlı fark gözlendi. Sonuç: Sonuçlarımız FMS'li hastaların fiziksel aktivite ve fiziksel uygunluk düzeyinin sağlıklı bireylere göre daha düşük olduğunu gösterdi

Objective: The aim of this study was to investigate the physical activity and physical fitness levels in patients with fibromyalgia syndrome (FMS) and to compare the data with those in healthy individuals.Methods: The study included 82 patients with FMS and 110 healthy individuals. In order to compare physical activity levels, all the subjects responded to the International Physical Activity Questionnaire, Long Form (IPAQ). The health-related physical fitness of the subjects was evaluated by body composition, muscle endurance, cardiorespiratory endurance, flexibility, and balance. Body mass index (BMI), sit-up test, 6-min walk test, sit and reach test, body lateral flexion, and Kinesthetic Ability Trainer 3000 (KAT 3000) were used to determine body composition, muscle endurance, cardiorespiratory endurance, flexibility, and balance, respectively.Results: Of the patients with FMS, 36.6% were inactive, 45.1% were insufficiently active, and 18.3% were active. Of the healthy individuals, 40.9% were active, 36.4% were insufficiently active, and 22.7% were inactive. Significant differences were found (p<0.05) in IPAQ walking and total scores between the groups. The sit-up test scores (p<0.001) and right and left body lateral flexion scores (p<0.001) were significantly different between the FMS patient and control groups.Conclusion: Our results showed that the physical activity and physical fitness levels of patients with FMS were lower than those of healthy individuals
Differences in Physical Activity and Physical Fitness Level in Patients with Fibromyalgia Syndrome and Healthy Individuals
Keywords: Fizyoloji; Rehabilitasyon; Spor Bilimleri